Quantitative Evaluation of Embolic Load in Femoral and Tibial Shaft Fractures Treated With Reamed Intramedullary Fixation. Issue 8 (August 2021) - Lee, Christopher; O'Hara, Nathan N.; Conti, Bianca; Hyder, Mary; Sepehri, Aresh; Rudnicki, Joshua; Hannan, Zachary; Connelly, Daniel; Baker, Mitchell; Pollak, Andrew N.; O'Toole, Robert V.
Abstract : Objectives: To compare the volume of embolic load during intramedullary fixation of femoral and tibial shaft fractures. Our hypothesis was that tibial intramedullary nails (IMNs) would be associated with less volume of intravasation of marrow than IM nailing of femur fractures. Design: Prospective observational study. Setting: Urban Level I trauma center. Patients/Participants: Twenty-three patients consented for the study: 14 with femoral shaft fractures and 9 with tibial shaft fractures. Intervention: All patients underwent continuous transesophageal echocardiography, and volume of embolic load was evaluated during 5 distinct stages: postinduction, initial guide wire, reaming (REAM), nail insertion, and postoperative. Main Outcome Measurements: Volume of embolic load was measured based on previously described luminosity scores. The embolic load based on fracture location and procedure stage was evaluated using a mixed effects model. Results: The IMN procedure increased the embolic load by 215% (−12% to 442%, P = 0.07) in femur patients relative to tibia patients after adjusting for baseline levels. Of the 5 steps measured, REAM was associated with the greatest increase in embolic load relative to the guide wire placement and controlling for fracture location (421%, 95% confidence interval: 169%–673%, P < 0.01). Conclusions: Femoral shaft IMN fixation was associated with a 215% increase in embolic load in comparison with tibial shaft IMN fixation, with the greatest quantitative load during the REAM stage; however, both procedures produce embolic load. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.